Deflection hardening behaviour of short fibre reinforced fly ash based geo-polymer composites - Shaikh, F.U.A. (Elsevier Ltd, 2013)
This paper reports the newly developed ductile fibre reinforced geopolymer composite (DFRGC) exhibiting deflection hardening and multiple cracking behaviour. The binder of the above composite is different from that used in conventional cement based system. The class F fly ash is used instead of Portland cement in DFRGC and is activated by alkaline liquids (sodium hydroxide and sodium silicate). In this study, two types of fibers namely steel (ST) and polyvinyl alcohol (PVA) fibres are used in mono as well as in ST-PVA hybrid form, with a total volume fraction of 2%. The deflection hardening behaviour of newly developed DFRGC is also compared with that of conventional ductile fibre reinforced cementitious composites (DFRCC). The effects of two different sizes of sand (1.18mm, and 0.6mm) and sand/binder ratios of 0.5 and 0.75 on the deflection hardening and multiple cracking behaviour of both DFRGC and DFRCC are also evaluated. Results revel that the deflection hardening and multiple cracking behaviour is achieved in geopolymer based DFRGC similar to that of cement based system. For a given sand size and sand content, comparable deflection hardening behaviour, ultimate flexural strength and the deflection at peak load are observed in both cement and geo-polymer based composites irrespective of fibre types and combination. The deflection hardening behaviour of DFRGC is also confirmed by the calculated toughness index values of I20>20. The scanning electron microscope (SEM) study shows no degradation of PVA and steel fibres in the geopolymer matrix. However, the bond of PVA fibre with geopolymer matrix is found to be higher than that with cement matrix as evidenced in the SEM pictures. An opposite trend is observed with steel fibre. The proposed development exhibit a significant benefit for the use of geopolymer based DFRGC over cement based system as the former one is green in terms of no cement use.